Students’ Attitudes and Beliefs Concerning University Classes of Philological Subjects - Wattles, Isidora M.; Radić-Bojanić, Biljana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Nowadays university, especially some faculties and departments, fight for survival in the market in many different ways, one of them being the increase in the number of students, which consequently affects the choice of teaching methods and class organization thus leading to heterogeneity in the classroom. The most important consequence of this diversity is the fact that each group of students comprises different individuals who differ in motivation, intellectual abilities and previous knowledge. These factors represent classroom problems that teachers have to tackle in order to achieve better learning outcomes for each student. This paper, therefore, relies on a qualitative research design conducted via an open-ended questionnaire, to investigate the students’ stance towards philological subjects, i.e. their attitudes and beliefs concerning teaching quality, student participation in the teaching process and their relationship towards studying. General conclusions indicate engaged thinking about classes and a need for clear and interactive classes, which is in accordance with the nature of philological studies and subjects, as well as modern views and recommendations about teaching.
Keywords: university; philological subjects; students; attitudes; beliefs